1990
DOI: 10.1007/bf00336212
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic risk factors for graft failure following pancreas transplantation: results of multivariate analysis of data from the International Pancreas Transplant Registry

Abstract: A multivariate analysis of prognostic factors for graft failure was performed on patients in the International Pancreas Transplant Registry. The analysis was restricted to the period January 1978 to June 1987 and included 764 patients. All patients had at least 1 year of follow-up. The following variables were studied: transplant year, continent (N. America, Europe, others), type of donor (cadaver, living related mismatched, living related HLA-identical), donor mismatch at the HLA A, B loci, donor mismatch at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
(1 reference statement)
1
3
0
Order By: Relevance
“…Most pancreas transplants are performed simultaneous with a kidney, and the benefit conferred by having akidney from the samedonor to monitor forrejection may override any advantage that one duct management technique has over another. The dominant effect of kidney association and the lack of a significant influence of duct management on outcome is consistent with a previous multivariate analysis of Registry data (Viste et al 1990).…”
Section: Discussionsupporting
confidence: 90%
“…Most pancreas transplants are performed simultaneous with a kidney, and the benefit conferred by having akidney from the samedonor to monitor forrejection may override any advantage that one duct management technique has over another. The dominant effect of kidney association and the lack of a significant influence of duct management on outcome is consistent with a previous multivariate analysis of Registry data (Viste et al 1990).…”
Section: Discussionsupporting
confidence: 90%
“…[17][18][19] However, acute pancreas rejection occurring within the first 6 months with cyclosporine (CsA) combined with corticosteroid and azathioprine (AZA), despite the use of induction therapy, remains the most important barrier to the success and safety of pancreas transplantation. 19,20 It has been shown that rejection episodes occur more frequently after pancreas-kidney transplantation compared with kidney transplantation alone, causing an increased in the rate of hospitalization, the use of antilymphocyte agents, and infection-related morbidity. [20][21][22][23] According to registry data, rejection accounts for 32% of graft failures in the 1st year after pancreas transplantation.…”
Section: Journal Of Clinical Pharmacology 2001;41:861-869 ©2001 the mentioning
confidence: 99%
“…19,20 It has been shown that rejection episodes occur more frequently after pancreas-kidney transplantation compared with kidney transplantation alone, causing an increased in the rate of hospitalization, the use of antilymphocyte agents, and infection-related morbidity. [20][21][22][23] According to registry data, rejection accounts for 32% of graft failures in the 1st year after pancreas transplantation. 15,16 However, improvements are expected to continue with the recent introduction of immunosuppressive agents tacrolimus (TAC) and mycophenolate mofetil (MMF).…”
Section: Journal Of Clinical Pharmacology 2001;41:861-869 ©2001 the mentioning
confidence: 99%
“…With the use of these drugs, most pancreas transplant centers reported rates of acute rejection ranging from 60 to 80% [4–19]. Risk factors for acute rejection included solitary pancreas transplantation, pancreas retransplantation, HLA mismatching, and the absence of antibody induction therapy [20–23]. However, recent developments in immunosuppressive therapy offer significant promise for reducing the risk of acute rejection and further enhancing long‐term graft survival.…”
Section: Maintenance Immunosuppressionmentioning
confidence: 99%